2015
DOI: 10.1002/bio.2846
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence study of Dy or Ce activated LiCaBO3 phosphor for γ‐ray and C5+ ion beam irradiation

Abstract: The photoluminescence and thermoluminescence characteristics of rare earths (Dy or Ce) activated LiCaBO3 phosphors have been studied. Phosphors were synthesized by modified solid state synthesis. The phosphors were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), photoluminescence (PL) and thermoluminescence (TL) for structural, morphological and luminescence studies. Dy(3+) activated LiCaBO3 shows emission at 486 and 577 nm due to (4) F9/2 →(6) H15/2 and (4) F9/2 → (6) H13/2 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The PL emission spectra of Dy 3+ ‐doped LiMgBO 3 sample excited at 349 nm wavelength is shown in Figure (b). The emission spectra consisted of two peaks centred at 478 nm and 572 nm that were due to the 4 F 9/2 → 6 H 15/2 magnetic dipole transition and the hypersensitive 4 F 9/2 → 6 H 13/2 electric dipole transitions, respectively of Dy 3+ . Furthermore, the inset in Figure (b) shows that emission intensity increased with increase in Dy 3+ concentration and did not show any concentration quenching until the 1 mol% concentration.…”
Section: Resultsmentioning
confidence: 94%
“…The PL emission spectra of Dy 3+ ‐doped LiMgBO 3 sample excited at 349 nm wavelength is shown in Figure (b). The emission spectra consisted of two peaks centred at 478 nm and 572 nm that were due to the 4 F 9/2 → 6 H 15/2 magnetic dipole transition and the hypersensitive 4 F 9/2 → 6 H 13/2 electric dipole transitions, respectively of Dy 3+ . Furthermore, the inset in Figure (b) shows that emission intensity increased with increase in Dy 3+ concentration and did not show any concentration quenching until the 1 mol% concentration.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, Kore et al (12) reported CaMg 3 (SO 4 ) 4 :Dy 3+ phosphor for carbon ion dosimetry, which shows 3.5 times more sensitivity than commercial CaSO 4 :Dy Thermoluminescent dosimeter (TLD) phosphor. Other researchers have also reported the use of phosphor in carbon ion dosimetry (13,14). Ce 3+ -activated LiCaAlF 6 is a well-known phosphor with diverse applications in solid-state tunable lasers and scintillators (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Kore et al (12) reported CaMg 3 (SO 4 ) 4 :Dy 3+ phosphor for carbon ion dosimetry, which shows 3.5 times more sensitivity than commercial CaSO 4 :Dy Thermoluminescent dosimeter (TLD) phosphor. Other researchers have also reported the use of phosphor in carbon ion dosimetry (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous applications of radiation in wide areas have motivated towards the development of radiation dosimetric materials according to the area of interest. Several luminescence based detectors (TLDs) were developed for the detection of radiation as well as quality control in radiation processing, and many novel dosimetric materials are still being researched . However, the saturation of TL response at high dose (above 1 kGy) of irradiation is a major concern for TL detectors like LiF:Mg,Cu,P, MgB 4 O 7 :Dy and CaSO 4 :Dy .…”
Section: Introductionmentioning
confidence: 99%